The Impact of Labor Migration: The International Molders and Allied Workers Union in Canada, 1860-1885 - Williams, C. (Relations industrielles / Industrial Relations, 1984)
This paper deals with some aspects in the relationships among Canadian molder locals, American molder locals and the binational organization.